Effect of tillage practices, fertilizer treatments and crop rotation on yield of maize (Zea mays L.) hybrids - Bramdeo, Karamchand; Rátonyi, Tamás (Acta Agraria Debreceniensis, 2020)
This research was conducted at the University of Debrecen Látókép Research Station and is part of an ongoing long-term polyfactorial experiment. The impact of three tillage systems (Mouldboard plowing-MT, Strip tillage-ST, Ripper tillage-RT) and two levels of fertilizer treatments (N80 kg ha-1, N160 kg ha-1) along with a control (N0 kg ha-1) on the yield of maize hybrids (Armagnac- FAO 490 & Loupiac-FAO 380) cultivated in rotation with winter wheat was evaluated during a two-year period (2017–2018). Amongst the three tillage treatments evaluated, ripper tillage (RT) had the highest average yield (10.14 t ha-1) followed by mouldboard tillage (MT) and strip tillage (ST) with 9.84 and 9.21 t ha-1 respectively. Yield difference between RT and MT was not significant (P>0.05), as compared to ST (P<0.05). Soil moisture content varied significantly with tillage practices and was highest in ST, followed by RT and MT (ST>RT>MT). Yield of RT was 7–9% higher than MT in monoculture plots, while MT reign superior in biculture plots (monoculture: RT>MT>ST; biculture: MT>RT>ST). A positive interaction between tillage and fertilization was observed, with higher yield variation (CV=40.70) in the non-fertilized (N0) plots, compared to those which received the N80 (CV=19.50) and N160 kg ha-1 (CV=11.59) treatments. Incremental yield gain from increase fertilizer dosages was significantly higher in monoculture, compared to biculture. There was no significant difference in yield between N160 and N80 in the biculture plots (12.29 vs 12.02 t ha-1). However, in monoculture plots, N160 yield was 23% higher than the N80 kg ha-1 (N160=11.74 vs N80=9.56 t ha-1). Mean yield of maize in rotation with winter wheat was 28% (2.47 tons) higher than monoculture maize. The greatest benefit of crop rotation was observed in the control plots (N0) with an incremental yield gain of 4.39 tons ha-1 over monculture maize (9.92 vs 5.43 t ha-1). Yield increased with higher fertilizer dosages in irrigated plots. Fertilizer application greatly increased the yield of maize and accounted for 48.9% of yield variances. The highest yield (11.92 t ha-1) was obtained with N160 kg ha-1 treatment, followed by N80 kg ha-1 (10.38 t ha-1) and N0 kg ha-1 (6.89 t ha-1) respectively. Overall mean yield difference between the two hybrids was not statistically significant, however, yield of FAO 380 was 3.9% higher (9.06 vs. 8.72 t ha-1) than FAO 490 in monoculture plots, while in biculture plots, FAO 490 was 4.1% higher than FAO 380. Average yield in 2018 was 13.6% (1.24 t ha-1) higher than 2017 for the same set of agrotechnical inputs, thus, highlighting the significant effect of cropyear. Armagnac (FAO 490) cultivated in rotation with winter wheat, under ripper tillage and N80 kg ha-1 is the best combination of treatments for optimum yield.